FATIGUE AND CORROSION PHENOMENON ON FAILURE OF WATER WALL TUBE BOILER - Eka Febriyanti; Amin Suhadi; Laili Novita Sari (BRIN, 2020)
Water wall tube is one of a boiler components which has a function to transform water to be vapour so that it is normally called steam generating tubes. Any failure on wall tube will affect to the whole boiler system. Â The purpose of this research is to find out root cause of failure of wall tube in order to avoid similar case in the future. Â Research is conducted by examining and testing the specimens on all aspects including visual, fractography, metallography, chemical analysis, hardness test and tensile test. Examination on the fracture surface by fractographic method found the evidence of fatigue fracture with the presence of beachmark. Another examination on uninstalled boiler tube shows indication of fabrication defect and trans-granular cracks which allowed corrosive agent infiltrated into the microstructure of the tube. However, the result of chemical analysis and tensile test indicated that the tubes investigated are in accordance with ASTM A 210 Grade C specifications. Therefore, the failure of the tube is not caused by wrong material selection, but through the combination of fatigue fracture and corrosion attack where initiated at fabrication defect that acted as stress raisers.